2014
DOI: 10.1542/peds.2013-3331
|View full text |Cite
|
Sign up to set email alerts
|

High Doses of Methylprednisolone in the Management of Caustic Esophageal Burns

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Corrosive substance ingestion is a public health issue in developing countries. Stricture formation is a late complication of corrosive substance ingestion. The role of corticosteroids in preventing corrosiveinduced strictures is controversial.WHAT THIS STUDY ADDS: High doses of methylprednisolone therapy lead to less frequent stricture formation in grade IIb esophageal burns in children who ingested caustic substances and may improve prognosis. abstract OBJECTIVE: Caustic substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 15 publications
0
46
0
10
Order By: Relevance
“…Methylprednisolone at a dose of 1 g/1.73 m 2 per day for 3 d showed benefit in reducing stricture development[25]. Likewise, dexamethasone (1 mg/kg per day) was shown to be better than prednisolone (2 mg/kg per day) in preventing stricture formation (38.9% vs 66.7%) and severe stricture development (27.8% vs 55.6%)[26].…”
Section: Managementmentioning
confidence: 99%
“…Methylprednisolone at a dose of 1 g/1.73 m 2 per day for 3 d showed benefit in reducing stricture development[25]. Likewise, dexamethasone (1 mg/kg per day) was shown to be better than prednisolone (2 mg/kg per day) in preventing stricture formation (38.9% vs 66.7%) and severe stricture development (27.8% vs 55.6%)[26].…”
Section: Managementmentioning
confidence: 99%
“…1,7,10 Çocuklarda korozif madde içimi kazaları gelişmekte olan ülkelerde gelişmiş ülkelere nazaran çok daha fazla görülmektedir. 2,4,7,[10][11][12][13][14][15][17][18][19][20][21][22][23][24] Gelişmekte olan ülkelerde yasal yaptırımların yeterince uygulanmaması nedeni ile korozif maddeler çocukların kolaylıkla açabileceği kaplarda satılmaktadır. Koruyucu hekimlik, bu kazaları etkili bir şekilde azaltmada yetersiz kalmaktadır.…”
Section: Korozi̇f Maddelerunclassified
“…[1][2][3][4][5][6][7][8][9][10] Bu kazalar, çocuk ve çocuk cerrahisi alanlarıyla doğrudan ilgili olmasının yanı sıra, toplum sağlığı ve koruyucu hekimlik açısından da ciddi bir konudur. 4,7,[11][12][13] Çocuklarda Korozif Madde İçimi:…”
unclassified
“…The duration of total parenteral nutrition was shorter in the steroid intervention group compared with the control group (p = 0.001). The authors concluded that high doses of methylprednisolone used for the management of grade II-b oesophageal caustic burns may reduce the risk of stricture [40][41][42].…”
Section: Treatmentmentioning
confidence: 99%